Simulation of the aging process of insulating systems variable frequency drive; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Garganeev A. G. Alexander Georgievich; Leonov A. P. Andrey Petrovich; Merkulov V. I. Valery Ivanovich; Charkov D. I. Dmitiy Igorevich (2016, 2016)
Title screen